Genome-Wide Identification of Genes Related to Biosynthesis of Phenolic Acid Derivatives in Bletilla striata at Different Suspension Culture Stages - Liu, Houbo; Huang, Ceyin; Li, Qingqing; Wang, Mufei; Xiao, Shiji; Shi, Junhua; He, Yihuai; Wen, Weie; Li, Lin; Xu, Delin (Frontiers in Plant Science, 2022)
To screen the genes regulate the biosynthesis of phenolic acid derivatives from the genome of Bletilla striata, the suspension culture system was constructed to sample the cells for the following experiments. Contents of four phenolic acid derivatives were determined by high performance liquid chromatography, several full-length transcriptome sequencings were performed on RNA samples at 10 time points for bioinformatics exploring. According to the correlation analysis, the key differential expressed genes (DEGs) related to biosynthesis of the four phenolic acid derivatives were detected and verified. The results showed that the contents of p-hydroxybenzylalcohol (HBA), DactylarhinA, Militarine and Coelonin reached the peak at 33 days post inoculation (Dpi), 18 Dpi, 39 Dpi and 39 Dpi of the culture system, respectively. Based on transcriptome data, 80 DEGs related to the biosynthesis of phenolic acid derivatives were obtained. KEGG pathway enrichment analysis mainly clustered them into 5 metabolic pathways, which were phenylpropane biosynthesis, starch and sucrose metabolic, cyanoamino acid metabolism, gluconeogenesis and glycolysis, phenylalanine metabolism. qPCR analysis showed that the relative gene expression levels were consistent with the overall trend of transcriptome sequencing results. Among them, 14, 18, 23 and 41 unigenes were found to be involved in the synthesis of HBA, DactylorhinA, Coelonin and Militarine, respectively. These unigenes laid a solid basis for elucidating the biosynthesis mechanism of phenolic acid derivatives in suspension cells of B. striata.